Programming with Java IDL. - Lewis, Geoffrey, 1956-; Barber, Steven; Siegel, Ellen (New York : John Wiley & Sons, Inc., 1998)
"This book is a guide to programming CORBA distributed objects in Java with Java IDL. This book is for developers who need to understand and work with systems that use both Java and CORBA, It's not only for people who work directly with the Sun Java IDL package, but also for people working with any CORBA Object Request Broker that conforms to the new OMG IDL-to-Java mapping specification. In this book, you will learn how to build systems using the technology that will become part of the foundation of future systems. CORBA object implementers will find this book useful for creating new shared services implemented in Java. Project managers and systems architects will find that this book is helpful in communicating the use of Java IDL without having to absorb all the minutiae in the specification itself, We hope that you will find the material in the book useful for both learning this technology and as a reference when you go on to build such systems of your own." (Copied from who should read this book?).
Introduction. Chapter 1. Java IDL and CORBA. Chapter 2. Java fundamentals. Chapter 3. Introduction to CORBA. Chapter 4. Distributed architecture concepts. Chapter 5. Getting to know Java IDL. Chapter 6. A basic Java IDL applet and server. Chapter 7. Internet polling. Chapter 8. InterPoll shared services. Chapter 9. The network pricing system: Building a distributed financial services application with Java IDL. Chapter 10. Server objects for the network pricing system. Chapter 11. Summary. Appendix A. IDL/Java language mapping. Appendix B. What´s on the programming with Java IDL web site? Index.
Keywords: JAVA -- PROGRAMMING LANGUAGE; CORBA -- COMPUTER ARCHITECTURE; COMPUTER ARCHITECTURES; INTERNET PROGRAMMING